Civic Power in Mining Conflicts: Barrier or Catalyst for a Just Energy Transition? - Anabel Marin; Gabriel Palazzo (Centre for Inclusive Trade Policy (CITP), University of Sussex Business School, 2025)
This paper explores the global landscape of civil resistance to mineral extraction and its implications for the political sustainability of the energy transition. As global demand for critical minerals accelerates in association with the energy transition, there is a growing imperative to secure mineral access while improving environmental and social outcomes. However, mining activities face significant resistance worldwide, posing major challenges to the justice and viability of the energy transition. Using an original dataset derived from the GDELT Project between 2015 and 2022, we provide the first systematic global mapping of conflict and cooperation in mining regions, spanning diverse socio-political contexts and offering novel insights into the economic, environmental, and justice-related drivers of these dynamics. Our findings reveal that resistance to mineral extraction is not confined to poorer, emerging economies but is instead widespread, occurring wherever mineral deposits are found, regardless of a country's income level. This resistance frequently reaches high levels of polarisation, often leading to costly delays and project cancellations. Although cooperation sometimes accompanies conflict, high-commitment cooperative actions are limited and less frequent in highly polarised situations. These insights highlight the need to move beyond traditional Corporate Social Responsibility (CSR) approaches and existing public participation efforts within Environmental Impact Assessments (EIAs). A just, sustainable, and democratic transition requires a deeper democratisation of investment decisions through inclusive governance frameworks that tackle the several injustices associated with mineral resource extraction.
Keywords: 330; energy transition; critical minerals; mineral extraction; social resistance; environmental justice; economic democracy; mining conflict